A study of the oxidation of FeCrAl alloy in pressurized water and high-temperature steam environment. (May 2015) - Park, Dong Jun; Kim, Hyun Gil; Park, Jeong Yong; Jung, Yang Il; Park, Jeong Hwan; Koo, Yang Hyun
Highlights: FeCrAl alloy was oxidized in pressurized 360 °C water and 1200 °C steam. Compared to Zr alloy, FeCrAl alloy showed much lower weight change after oxidation. FeCrAl alloy showed weight loss or gain depending on test conditions. Fe2 O3 was mainly formed on the surface of FeCrAl alloy after 360 °C corrosion test. Al2 O3 was mainly formed on the surface of FeCrAl alloy after 1200 °C oxidation test. Abstract: The oxidation behaviour of the FeCrAl alloy under normal operating conditions of a light water reactor is reported. In a comparative study, Zr-based and FeCrAl alloy samples were corroded in pressurized 360 °C water for up to 500 days or oxidized at 1200 °C for 3000 s in a steam environment. Compared to Zr-based alloys, the FeCrAl alloy showed extremely low weight change after both tests. The microstructure of the oxides formed on FeCrAl alloys was characterized by various analysing techniques. It was concluded that depending on the test conditions, mostly different oxide phases of α-Fe2 O3 and α-Al2 O3 were formed.